Facile Synthesis of Large Wrinkled Gold Nanoparticles Using Anthracene‐Terminated Tripodal Amine Ligand and their Catalytic Efficiency. Issue 48 (26th October 2020) - Devi, Manisha; Dhir, Abhimanew; Pradeep, Chullikkattil P.
Abstract : A controlled bottom up approach for the synthesis of gold nanoparticles (AuNPs) with wrinkled surface morphology is rarely reported. Herein, an anthracene‐terminated tripodal amine (1 ) has been explored as capping ligand in the synthesis of AuNPs. Addition of Au 3+ ions to a solution of 1 leads to complex formation as revealed by the quenching of the ligand fluorescence. Controlled addition of ascorbic acid to this solution leads to de‐complexation and regeneration of the ligand fluorescence. Addition of excess ascorbic acid leads to the reduction of the recovered gold to AuNPs. The TEM analyses revealed ca. 3–4 nm size range for the as‐synthesized AuNPs in solution, which, over a period of time, agglomerate to large AuNPs of size ca. 300–400 nm with wrinkled surface morphology as revealed by SEM analyses. Control experiments performed using similar tripodal amine ligands terminated with pyrene (2 ) and naphthalene (3 ) yielded comparatively smooth surfaced AuNPs agglomerates revealing that the ligand 1 plays an important role in the formation of the wrinkled AuNPs. Further, the catalytic reduction of 4‐nitrophenol performed using these AuNPs showed that the AuNPs generated by the ligand 1 exhibit better catalytic rate, probably because of their increased surface area due to the wrinkled morphology. Abstract : An anthracene based tripodal amine has been employed as capping ligand for the generation of AuNPs in solutions, which further agglomerate into big AuNPs with wrinkled surface morphology. The AuNPs with wrinkled surface morphology showed enhanced catalytic activity towards the reduction of 4‐nitrophenol to 4‐aminophenol in comparison to the smooth surfaced AuNPs.